Implementasi Project Based Learning dalam Mengembangkan Pola Pikir Kritis Siswa di SDN 063/VI Rejosari - Nela Silvia; Rita Rahmatillah; Yusrizal Yusrizal; Siti Annisa (FKIP Universitas Islam Jember, 2026)
Contemporary learning requires elementary school students to possess critical thinking skills as a fundamental competence to address various challenges. However, classroom practices at the elementary level are still largely teacher-centered, which limits students’ active involvement in constructing and developing these skills. Project Based Learning (PjBL) is considered an appropriate instructional approach to address this issue, as it actively engages students in problem-solving activities through project-based tasks. This study aims to analyze the implementation of PjBL and its role in enhancing elementary students’ critical thinking skills. The research employed a descriptive qualitative method and was conducted at SDN 063/VI Rejosari, Muaro Regency. The findings indicate that the implementation of PjBL enhances students’ active participation in the learning process and encourages them to ask questions and express their ideas confidently. Furthermore, students’ critical thinking skills improved, as reflected in their ability to identify problems, formulate questions, provide logical reasoning, and draw well-founded conclusions. Therefore, PjBL can serve as an effective alternative learning model to support the development of critical thinking skills in elementary school students.